Evaluasi Kualitas Sensoris Kopi Robusta Berdasarkan Variasi Pengeringan dan Suhu Penyangraian - Fahlan Khuluq; Edi Wiraguna (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
Robusta coffee is one of Indonesia's leading commodities with high economic value. The flavor quality of coffee is greatly influenced by post-harvest processes, particularly drying methods and roasting temperatures. This study aims to determine the effects of two drying methods—Viss Dryer and Mason Dryer—and three roasting temperatures (190°C, 197°C, and 200°C) on the flavor profile of robusta coffee at PTPN I Regional 5 Kebun Malangsari. The evaluation was conducted through cupping tests by trained and untrained panelists. Parameters assessed included aroma, flavor, aftertaste, salt/acid, mouthfeel, and balance. The results showed that roasting temperature significantly affected aroma and flavor, with 200°C yielding the highest scores across panelist groups. Drying methods had a more limited effect; trained panelists preferred coffee dried with the Mason Dryer, whereas untrained panelists favored coffee dried with the Viss Dryer. Other parameters such as aftertaste, salt/acid, mouthfeel, and balance showed no significant differences among treatments. The optimal combination, based on trained panelists’ evaluations, was achieved using the Mason Dryer with a roasting temperature of 200°C. These findings underscore the importance of precise roasting temperature control in enhancing the sensory quality of robusta coffee and reveal how panelist experience levels can influence sensory preferences for drying methods. The results provide practical insights for post-harvest coffee processing to improve product quality and competitiveness in both national and international markets.